Understanding the Differences in Tobacco Circulation Laws: A Comparative Study Between France and Indonesia - Ainun Qadisah , Altares; Sulistianingsih, Dewi; Putu Rahayu, Sang Ayu (The Indonesian Journal of International Clinical Legal Education, 2024)
This research aims to conduct a comparative analysis of the legal regulations governing the circulation of cigarettes between France and Indonesia. By examining the existing legal frameworks in both countries, this study highlights the differences and similarities in the legal approaches towards the tobacco industry, including regulations on advertising, sales, and taxation of cigarettes. Through careful data collection and analysis, this article offers an in-depth understanding of how the laws and policies of each country influence the circulation of cigarettes and their impact on public health. The implications of these legal differences are also considered to enhance the understanding of international regulations related to tobacco control. The research results show that regulating the circulation of cigarettes is an important issue for many countries in their efforts to protect public health. Although France and Indonesia share the same goal, the regulatory approaches adopted by these two countries differ. France implements very strict regulations, such as bans on cigarette advertising, promotion, and sponsorship, restrictions on the sale of cigarettes to people under 18 years of age, as well as high excise and tax policies. On the other hand, Indonesia takes a more moderate approach by considering the economic aspects of the tobacco industry. However, both countries still face challenges in implementing and enforcing these regulations. Cross-country cooperation and participation in international forums, such as the Framework Convention on Tobacco Control (FCTC), can be a solution to strengthen global efforts to protect public health.